2013
DOI: 10.1111/soc4.12022
|View full text |Cite
|
Sign up to set email alerts
|

The Social Aspects of Xenotransplantation

Abstract: Xenotransplantation is a controversial medical science where living animal parts are transplanted into humans. While the literature on xenotransplantation is vast in regards to medical and scientific research, and ethics, it is comparatively lacking in social science. This article examines the literature on the social aspects of xenotransplantation, with a focus on public perception, ontology and identity, meat, knowledge production, animal bodies and scientific knowledge. This demonstrates that the science se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Several recent advances in XTx research, particularly those associated with genetic engineering of the organ source pig, may be particularly applicable in the neonatal population whose immune system is immature. 4 While most work in XTx has been focused on its scientific and ethical aspects, 5,6 to our knowledge, no known studies have addressed the attitudes to XTx among surgeons/physicians who care for patients in need of cardiac transplantation. Physician engagement is particularly important, as their support for a particular procedure is crucial to patients’ medical decision-making and care.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent advances in XTx research, particularly those associated with genetic engineering of the organ source pig, may be particularly applicable in the neonatal population whose immune system is immature. 4 While most work in XTx has been focused on its scientific and ethical aspects, 5,6 to our knowledge, no known studies have addressed the attitudes to XTx among surgeons/physicians who care for patients in need of cardiac transplantation. Physician engagement is particularly important, as their support for a particular procedure is crucial to patients’ medical decision-making and care.…”
Section: Introductionmentioning
confidence: 99%
“…There are concerns that some societies will oppose pig-to-human xenotransplantation because of religious and cultural aspects [ 140 ]. Moreover, there is a probability that the use of organs from modified pigs, in some countries, may lead to a global trend of reducing the number of human transplants for altruistic reasons [ 141 ]. At this moment, we are unable to predict the reaction of society to a person carrying an animal organ.…”
Section: Xenotransplantationmentioning
confidence: 99%
“…To demonstrate the xenotransplantation paradox (that is, 'nonhuman animals are the same as humans but different') I begin reviewing research on patient, health professional and public attitudes that have consistently demonstrated negativity towards xenotransplantation ( Appel III, Alwayn, and Cooper 2000 ; Bona et al 2004 ; Brown 1999 ; Brown and Michael 2004 ; Butler 1998 ; Canova et al 2006 ; Conesa et al 2006 ; Cook 2013 ; Fovargue 2007 ; Hagelin 2004 ; Lundin 2002 ; Lundin and Idvall 2003 ; Lundin and Widner 2000 ; Macer et al 2002 ; Martinez-Alarcon et al 2005 ; Michael and Brown 2004 ; Mohacsi et al 1995 ; Mohacsi et al 1997 ; Mohacsi, Thompson, and Quine 1998 ; Persson et al 2003 ; Rios et al 2007 ; Sanner 2005 ; Schlitt et al 1999 ). At present, pigs are thought to be an ideal source for transplantation into humans as their internal organs are similar in size to humans but this is not often identified as the organ donor host in previous research.…”
Section: Introductionmentioning
confidence: 99%